2018
DOI: 10.1155/2018/7287820
|View full text |Cite
|
Sign up to set email alerts
|

Tualang Honey Reduced Neuroinflammation and Caspase‐3 Activity in Rat Brain after Kainic Acid‐Induced Status Epilepticus

Abstract: The protective effect of tualang honey (TH) on neuroinflammation and caspase-3 activity in rat cerebral cortex, cerebellum, and brainstem after kainic acid- (KA-) induced status epilepticus was investigated. Male Sprague-Dawley rats were pretreated orally with TH (1.0 g/kg body weight) five times at 12 h intervals. KA (15 mg/kg body weight) was injected subcutaneously 30 min after last oral treatment. Rats were sacrificed at 2 h, 24 h, and 48 h after KA administration. Neuroinflammation markers and caspase-3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 93 publications
0
23
0
Order By: Relevance
“…In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46]. In kainic acid-induced excitotoxicity animal model, pretreatment with honey significantly attenuated oxidative stress, neuroinflammation, and apoptosis in the cerebral cortex, cerebellum, and brainstem as well as progression of neuronal damage in the piriform cortex of kainic acid-induced rats [47][48][49]. Hence, honey confers its neuroprotection against the deleterious effect of kainic acid through its antioxidants and anti-inflammatory and antiapoptotic properties, thereby protecting brain from neuronal loss and neurodegeneration.…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…In general, pure honey contains over 200 compounds, consisting mainly of carbohydrates (monosaccharides: glucose and fructose; disaccharides: sucrose and maltose), protein (amino acids and enzymes), minerals, vitamins (vitamin B6, riboflavin, niacin, and thiamine), phenolic compounds (flavonoids and phenolic acids), and volatile substance (responsible for the characteristic aroma of honey) [41][42][43][44][45][46]. In kainic acid-induced excitotoxicity animal model, pretreatment with honey significantly attenuated oxidative stress, neuroinflammation, and apoptosis in the cerebral cortex, cerebellum, and brainstem as well as progression of neuronal damage in the piriform cortex of kainic acid-induced rats [47][48][49]. Hence, honey confers its neuroprotection against the deleterious effect of kainic acid through its antioxidants and anti-inflammatory and antiapoptotic properties, thereby protecting brain from neuronal loss and neurodegeneration.…”
Section: Neuroprotective Activities Of Natural Products and Their Biomentioning
confidence: 99%
“…Tualang honey also demonstrated anti-inflammatory properties; pretreatment with Tualang honey reduced neuroinflammation by reducing the elevation of TNF-α, IL-1β, glial fibrillary acidic protein, allograft inflammatory factor 1 and COX-2 in the rat cerebral cortex, cerebellum and brainstem in kainic acid (KA)-induced status epilepticus rat [ 103 ]. Another study also reported a reduction in TNF-α, IL6 and IFN-γ in the brain homogenates of a Tualang honey-treated chronic stress rat model [ 104 ].…”
Section: Medicinal Properties Of Tualang Gelam and Kelulut Honeysmentioning
confidence: 99%
“…In a study of kainic acid KA-treated rats, pretreatment with Tualang honey reduced the KA-induced neuronal degeneration in the piriform cortex but failed to prevent the occurrence of KA-induced seizures. In addition, KA-induced rats showed increased locomotor activity and hyperactivity, which were attenuated by Tualang honey pretreatment [ 103 ]. A recent study reported that Tualang honey pretreatment significantly attenuated an increase in lipid peroxidation level and decreased the total antioxidant status level induced by KA treatment in the rat cerebral cortex.…”
Section: Medicinal Properties Of Tualang Gelam and Kelulut Honeysmentioning
confidence: 99%
“…Honey is a beehive product which elicits its neuroprotective action against the unfavorable effect of kainic acid via its antioxidant and anti-apoptotic properties, thus preventing neuronal loss and neurodegeneration in the brain. Pretreatment with honey attenuates neuroinflammation, OS, and apoptosis in the cerebellum, cerebral cortex, and brainstem in kainic acid-induced rats [ 147 ]. Another bee product, propolis, has been shown to attenuate caspase-3 activity and NO level and inhibit the neuronal loss against excitotoxicity caused by kainic acid in a rat model.…”
Section: Nutraceuticals In Nds: Multi-targeted Avenuementioning
confidence: 99%